Sex and gender differences in hepatitis C virus risk, prevention, and cascade of care in people who inject drugs: systematic review and meta-analysisResearch in context - Anna Levinsson; Camille Zolopa; Farzaneh Vakili; Sasha Udhesister; Nadine Kronfli; Mathieu Maheu-Giroux; Julie Bruneau; Heather Valerio; Sahar Bajis; Phillip Read; Elisa Martró; Lisa Boucher; et al. (EClinicalMedicine, 2024)
Summary: Background: People who inject drugs (PWID) are a priority population in HCV elimination programming. Overcoming sex and gender disparities in HCV risk, prevention, and the cascade of care is likely to be important to achieving this goal, but these have not yet been comprehensively reviewed. Methods: Systematic review and meta-analysis. We searched Pubmed, EMBASE and the Cochrane Database of Systematic Reviews 1 January 2012–22 January 2024 for studies of any design reporting sex or gender differences among PWID in at least one of: sharing of needles and/or syringes, incarceration history, injection while incarcerated, participation in opioid agonist treatment or needle and syringe programs, HCV testing, spontaneous HCV clearance, direct-acting antiviral (DAA) treatment initiation or completion, and sustained virological response (SVR). Assessment of study quality was based on selected aspects of study design. Additional data were requested from study authors. Data were extracted in duplicate and meta-analysed using random effects models. PROSPERO registration CRD42022342806. Findings: 9533 studies were identified and 92 studies were included. Compared to men, women were at greater risk for receptive needle and syringe sharing (past 6–12 months: risk ratio (RR) 1.12; 95% confidence interval (CI) 1.01–1.23; <6 months: RR 1.38; 95% CI 1.09–1.76), less likely to be incarcerated (lifetime RR 0.64; 95% CI 0.57–0.73) more likely to be tested for HCV infection (lifetime RR 1.07; 95% CI 1.01, 1.14), more likely to spontaneously clear infection (RR1.58; 95% CI 1.40–1.79), less likely to initiate DAA treatment (0.84; 95% CI 0.78–0.90), and more likely to attain SVR after completing DAA treatment (RR 1.02; 95% CI 1.01–1.04). Interpretation: There are important differences in HCV risk and cascade of care indicators among people who inject drugs that may impact the effectiveness of prevention and treatment programming. Developing and assessing the effectiveness of gender-specific and gender-responsive HCV interventions should be a priority in elimination programming. Funding: Réseau SIDA-MI du Québec.